Der Einfluß temporärer Arbeitsmigration auf die Agrarentwicklung in der arabischen Republik Jemen - Kopp, Horst (ERDKUNDE, 1977)
Temporary emigration has a long tradition in Yemen. Since the oil-boom in the neighbouring countries it has strongly increased so that at this moment every second occupied Yemenite is working abroad. Because of the resilient and intimate tribal bonds emigrants nearly always return to their villages. The earned money is mostly in vested in housebuilding; at the same time fields decay as rural manpower is lacking.